ANALISIS KEWENANGAN BAWASLU KABUPATEN JEMBER DALAM MENANGANI PELANGGARAN PEMILIHAN BUPATI DAN WAKIL BUPATI TAHUN 2020 DI TENGAH PANDEMI COVID 19 - Dwi Hastuti; Wildan Rofikil Anwar (Indonesian Journal of Law and Islamic Law (IJLIL), 2021)
The 2020 elections, including the electoral of Regent and Deputy Regent of Jember Regency, are different from the electoral in the previous year because of the COVID-19 pandemic that created many challenges in election supervision, especially the handling of election violations. Therefore, This study aims to determine the role and constraints of Bawaslu in handling violations of the election of regents and deputy regents during the covid 19 pandemic. This research uses a qualitative type with a case study approach. And data collection techniques through in-depth interviews and documentation. The study found that the Jember Regency Bawaslu does its authority based on Act No. 7 of 2017, Act No. 10 of 2016. And Regulation of Bawaslu No 8 of 2020. The Jember Regency Bawaslu supervises the implementation of the election and also makes efforts to prevent violations in the election of the Regent and Deputy Regent in the era of the COVID-19 pandemic. But there are still various violations:  one case of criminal offenses, two cases of administrative violations, one case of the code of ethics violation, and four cases of  health protocols violations. Obstacles of handling violations of the election are the content of the Bawaslu Regulation No. 8 of 2020, and structural obstacles are inadequate human resources and disagreements in the Gakkumdu center, cultural obstacles are money politics culture, nepotism culture, and patron clients culture.The 2020 elections, including the electoral of Regent and Deputy Regent of Jember Regency, are different from the electoral in the previous year because of the COVID-19 pandemic that created many challenges in election supervision, especially the handling of election violations. Therefore, This study aims to determine the role and constraints of Bawaslu in handling violations of the election of regents and deputy regents during the covid 19 pandemic. This research uses a qualitative type with a case study approach. And data collection techniques through in-depth interviews and documentation. The study found that the Jember Regency Bawaslu does its authority based on Act No. 7 of 2017, Act No. 10 of 2016. And Regulation of Bawaslu No 8 of 2020. The Jember Regency Bawaslu supervises the implementation of the election and also makes efforts to prevent violations in the election of the Regent and Deputy Regent in the era of the COVID-19 pandemic. But there are still various violations:  one case of criminal offenses, two cases of administrative violations, one case of the code of ethics violation, and four cases of  health protocols violations. Obstacles of handling violations of the election are the content of the Bawaslu Regulation No. 8 of 2020, and structural obstacles are inadequate human resources and disagreements in the Gakkumdu center, cultural obstacles are money politics culture, nepotism culture, and patron clients culture.